2007
DOI: 10.1111/j.1365-2125.2007.02958.x
|View full text |Cite
|
Sign up to set email alerts
|

Society already achieves economic benefits from generic substitution but fails to do the same for therapeutic substitution

Abstract: AimsTo assess the potential annual savings due to generic and therapeutic substitution of statin therapy for the general Dutch population, taking the patients medical history into account. MethodsWe conducted a population-based costing study using the PHARMO Record Linkage System (RLS). PHARMO RLS contains drug dispensing records from a representative sample of pharmacies located in more than 50 regions in the Netherlands. We selected all statin users in the database since 2003. The cost-savings of generic sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
(6 reference statements)
0
21
0
Order By: Relevance
“…Significantly less statins were dispensed (based on DDDs/1,000 patients) in Northern Ireland compared with the matched region in England both before (19,866 vs. 32,432; P \ 0.001) and after the introduction of QOF (32,757 vs. 42,716; P \ 0.001). However, significantly more statins were dispensed in both regions after the introduction of QOF (52,623 DDDs/1,000 patients rising to 75,148 DDDs/1,000 patients) ( Table 2).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Significantly less statins were dispensed (based on DDDs/1,000 patients) in Northern Ireland compared with the matched region in England both before (19,866 vs. 32,432; P \ 0.001) and after the introduction of QOF (32,757 vs. 42,716; P \ 0.001). However, significantly more statins were dispensed in both regions after the introduction of QOF (52,623 DDDs/1,000 patients rising to 75,148 DDDs/1,000 patients) ( Table 2).…”
Section: Resultsmentioning
confidence: 95%
“…This highlights once more the power of generic prescribing in cost containment [17]. Finally, in a recent study in the Netherlands, Gumbs et al concluded that society could benefit from an economic point of view by employing a dual strategy of both therapeutic substitution and generic substitution [19]. The differences in total statin prescribing (DDDs/1000 patients) pre and post QOF in NY Fig.…”
Section: Discussionmentioning
confidence: 95%
“…In general, from an economic point of view, society could gain a lot from substituting statin therapy, especially from therapeutic substitution [29]. Moreover, prescribing generic or preferred medications within a therapeutic class was associated with improvements in adherence to therapy [30].…”
Section: Final Conclusionmentioning
confidence: 99%
“…Price reductions in the offpatent market can also be achieved by generic substitution or generic prescribing [12][13][14].…”
Section: Introductionmentioning
confidence: 99%